2021
DOI: 10.1109/access.2021.3070198
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Antenna Arrays for Spatial Multiplexing: Towards 6G Systems

Abstract: In this paper we discuss the design of antenna arrays to be used for multiplexing applications. In particular, we introduce a suitable performance index to analyze the effect of the antenna geometry and the distribution of users for the overall performance of Multi-User Multiple Input Multiple Output systems. By means of such performance index, antenna arrays can be designed so as to increase the number of multiplexed parallel sub-channels . Numerical results show that a proper design could allow to double the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 73 publications
1
20
0
Order By: Relevance
“…In [15], it was shown that data streams became less correlated when the inter-element spacing was increased, regardless of the appearance of grating lobes. In [16], a similar finding was obtained, where it was shown that the overall data rate was improved when employing a sparse regular array rather than a dense one. This conclusion was also reached in [17], where in addition to regularly spaced arrays, an irregularly spaced array with 200 antenna elements was considered.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…In [15], it was shown that data streams became less correlated when the inter-element spacing was increased, regardless of the appearance of grating lobes. In [16], a similar finding was obtained, where it was shown that the overall data rate was improved when employing a sparse regular array rather than a dense one. This conclusion was also reached in [17], where in addition to regularly spaced arrays, an irregularly spaced array with 200 antenna elements was considered.…”
Section: Introductionsupporting
confidence: 70%
“…A similar conclusion was reached in [15], where it was shown that sparse arrays led to a lower probability that the streams of two users became correlated. In [16], it was shown that an improvement of the stability of the inversion in (6) occurred when the antenna elements were spaced in a sparse regular fashion. This was also in line with the result that was found here, since the outages occurred whenever the matrix HH † became singular (i.e., the matrix was unstable).…”
Section: Regular Arraysmentioning
confidence: 99%
“…Simultaneously the network operators are maximizing their LTE network by applying LTE-Advacned for providing capacity scalability and also to make it felxibile to adpot cellular connectivity. Recently, the mobile traffic increased drastically (also by changes induced by COVID- VOLUME 4, 2016 19) which allows antennas to further optimize towards 6G systems [21]. For 5G systems to be reliable RF propagation models have to be generated to ensure standard performance which also includes path loss models [22], [23].…”
Section: Introductionmentioning
confidence: 99%
“…This approach expands beam-forming and spatial filtering and allows the reuse of time and frequency resources with a low level of user interference. Optimization of the antenna array to obtain maximum performance in Line-of-Sight (LoS) propagation condition was explored in [21], introducing a predictor factor for beam-forming losses and a way to use it in MU-MIMO systems. Moreover, grating lobes did not have a negative impact in MU-MIMO systems, while using larger inter-element spacings can be advantageous.…”
Section: Introductionmentioning
confidence: 99%